Characterization and Amelioration of Selected Acid Sulfate Soils in Malaysia - Sarwani, Muhrizal (2001)
Researchers in the past had focused their study on the common or standard acid sulfate soils, which are characterized by high iron and the presence of jarosite mottles. Little is known about the characteristics and management of iron-poor acid sulfate soils and this study was conducted to provide the dearth of information. This study aimed to characterize and ameliorate acid sulfate soils in Malaysia. Three common acid sulfate soils in Malaysia namely Teluk, Jawa and Linau series were investigated in three phases. The first phase was concentrated on the characterization of the soils. The second phase dealt with laboratory incubation experiments to study oxidation processes. The third phase was on the ameliorative effects of organic materials, lime, phosphate and silicate application on acid sulfate soils. Results of the study revealed the presence of both iron-rich and iron-poor acid sulfate soils in Malaysia. The former, represented by the Teluk and Jawa soils, had thick accumulation of iron in the B-horizon. They followed the standard morphological profile commonly found under tropical monsoon climate. The latter, represented by the Linau soil, was low in iron content in the B-horizon. They followed the standard morphological profile commonly found under tropical monsoon climate. The latter, represented by the Linau soil, was low in iron content in the B-horizon. The low content of iron was most probably due to high organic content enhanced by wet climate in Malaysia. The formation of Fe (III) oxide was hindered when the environment was rich in organics. Incubation study indicated that oxidation of pyrite resulted in a decrease in pH and the formation of jarosite which, in tum, transformed into short-range order Fe-oxides. The yellow mottles formed during pyrite oxidation were jarosite/natrojarosite and alunite as detected by X-ray diffraction analysis. The oxidation of pyrite was retarded by addition of phosphate and silicate. The retardation of pyrite oxidation was probably due to coating of insoluble materials on the pyrite surface.